WANPRESTASI PERJANJIAN PERJALANAN WISATA LUAR NEGERI OLEH WISATAWAN INDONESIA - Putri Kusuma Sanjiwani; Ni Luh Kerti Pujani (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
The development of tourism, supported by a breakthrough in the development of industry 4.0, has brought great changes to people in all parts of the world.Tourism is a secondary need for millennial today. They have different motivations individually towards the destination they dream of. People who buy overseas travel packages in travel agents have an escape mode by separating themselves from the tour group at certain destinations.The writing method used in this study is empirical legal research methods supported by primary and secondary data with data collection techniques carried out by observation, interviews, and literature studies.The form of default carried out by Indonesian tourists is classified as doing something in an agreement that is prohibited/ cannot be done.Defaults are made by tourists who will separate themselves from the group and disappear during the tour.They do not return to the hotel or appear within 24 hours so they can be declared lost and reported missing.This activity can broaden the image of the Unitary State of Indonesia in general and the image of travel agents in particular.There needs to be coordination between the community, the government and businessmen of travel agents in suppressing the practices or activities of illegal immigrants.